Gender and vulnerable types among vulnerable member in Malaysia fisheries and aquaculture community - Zainalaludin, Zumilah; Jamaluddin, Askiah; Abd Shukor, Suryati; Saidi, Norehan (International Journal of Children, Women, Elderly and Disable People, 2017)
The objective of this paper is to explore any different on vulnerability type (VuT) by sex of vulnerable community member (VCM) among aquaculture and fisheries households in Malaysia. There were qualitative and quantitative methods used in this paper – Focus Group Discussion (FGD) and survey. Initially, eight conceptual definitions obtained in literatures on economically vulnerable due to poverty and disable to work and earn income – i) older person, ii) poor single mother/father, iii) handicapped person, iv) career of bed ridden patient, v) suffering of serious illness (diabetic, heart problem, kidney failure, hypertension, and cancer), vi) poor and living alone, vii) child labor, and viii) others. A questionnaire was specially developed for this study and was distributed to 60 community leaders (CL) (the head of the village - JKKK) to give the profiles of 5-6 VCMs from different household in his village. These CLs are the informant of the FGD session. There are three sub-districts in this study – Kuala Kedah, Alor Star, Kuah and Air Hangat, Langkawi Kedah. These three sub-districts were purposely sampled to differentiate between 2-background of Fisheries and Aquaculture communities (FAC) – a mainland (Kuala Kedah) and an island (Langkawi). There are 42 males and 99 females VCMs had suggested by 60 community leaders in the questionnaire. Beside the questionnaire, 12 FGD sessions were conducted in 6-session for male JKKK (33 males) and 6-session female JKKK (27 females) in two different places in order to capture VuT. The 6-VuT are significant with the sex of VCM (p<0.05) through Chi Square test after the 8-VuT was regrouped. There are high percentage among male VCM is the disable male (38.1%) than disable female (14.1%); and high percentage among female VCM is single mother (37.4%) as only 9.5% single father. Second high percentage among male VCM is ‘others’ category (21.4%) and for female VCM is poor older person (15.2%). The FGD discussion obtained the answer of the ‘others’ category which may refer to drug addict and refugees. This may answer the second high percentage of male VCM in ‘others’ category of VuT.